2012
DOI: 10.1080/00380768.2012.723603
|View full text |Cite
|
Sign up to set email alerts
|

Impact of molybdenum on Chinese cabbage response to selenium in solution culture

Abstract: Molybdenum (Mo) and selenium (Se) are both essential micronutrients for animals and humans. Increasing Mo and Se contents in food crops offers an effective approach to reduce Mo and Se deficiency problems. A hydroponic trial was conducted to investigate the interactions of Mo and Se on uptake, transfer factors (TF shoot ) as well as distribution coefficients (DC) of Mo and Se on Chinese cabbage (Brassica campestris L. ssp. Pekinensis). In Experiment 1 three concentrations of Mo (0.01, 0.1 and 1 mg L À1 ) and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 28 publications
(24 reference statements)
1
10
0
Order By: Relevance
“…In wheat, Mo supplementation increased the activities and transcripts of antioxidant enzymes, decreased H 2 O 2 and MDA contents, and elevated NO production, implying that Mo-induced antioxidant defense may be related to NO signal [ 43 ]. Zhang et al, reported that when Se and Mo were used independently in the growth medium at 0.01 mg/L concentration, it slightly enhanced the growth of Chinese cabbage, however, at slightly higher Se concentration 0.1 mg/L, it significantly reduces the plant growth as indicated by more than 10% decrease in shoot DW, as compared to using Mo only [ 44 ]. The reduction in plant biomass in case of combined Se and Mo application can be due to more than one reason.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In wheat, Mo supplementation increased the activities and transcripts of antioxidant enzymes, decreased H 2 O 2 and MDA contents, and elevated NO production, implying that Mo-induced antioxidant defense may be related to NO signal [ 43 ]. Zhang et al, reported that when Se and Mo were used independently in the growth medium at 0.01 mg/L concentration, it slightly enhanced the growth of Chinese cabbage, however, at slightly higher Se concentration 0.1 mg/L, it significantly reduces the plant growth as indicated by more than 10% decrease in shoot DW, as compared to using Mo only [ 44 ]. The reduction in plant biomass in case of combined Se and Mo application can be due to more than one reason.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, when Mo is applied with Se, it enhances Se transport from shoot to root and increases Se concentration in root and reduce it in shoot. Zhang et al [ 44 ] found an antagonistic relationship between Se and Mo uptake in Chinese cabbage when both were supplied in solution culture. Se concentrations in shoots and roots were significantly inhibited by application of Mo.…”
Section: Discussionmentioning
confidence: 99%
“…The antagonistic or synergistic effect of Se has been studied primarily in human or animal nutrition, with far less research on plant nutrition. Antagonism has been detected between Se and sulphur [34], Se and mercury [35] and Se and molybdenum [36]. The relationship of Se with arsenic species [37,38] and cadmium [39,40] was also studied and found to be either synergistic or antagonistic.…”
Section: Introductionmentioning
confidence: 99%
“…Biofortification is a method to produce plant products rich in certain elements that are otherwise deficient, but the concentration of other nutrients important for human consumption should not be adversely affected. The antagonistic effect of Se on elements such as sulphur, mercury and molybdenum has been shown in previous studies [71][72][73]. However, for most elements, the results have been conflicting, often depending on whether Se was applied to soil or hydroponic growing medium (nutrient solution culture) [74] or as a leaf spray [75].…”
Section: Changes In Element Compositionmentioning
confidence: 93%